LEGAL OUTLINE FOR PRODUCTION AND MARKET OF ORGANIC FOOD IN EU AND SCG - Mirjana Savic; Nada Mijajlovic; Branko Katic (Ekonomika Poljoprivrede (1979), 2006)
In the last decade of twentieth centaury number of organic producers is increasing. At the same tike demand and consumption are in constant increasing and they are higher than offer of these products.